Towards music-driven procedural animation - Brito, Carlos Faria Aquino (2019)
We present our approach towards the development of a framework for the creation of music-driven procedural animations. We intend to explore the potential that elementary musical features hold for driving engaging audio-visual animations. To do so, we bring forward an integrated environment where real-time musical information is available and may be flexibly used for manipulating different aspects of a dynamic animation. In general terms, our approach consists of developing a virtual scene, populated by controllable entities, termed actors, and using scripting to define how these actors' behaviour or appearance change in response to musical information. Scripting operates by establishing associations, or mappings, between musical events, such as the ringing of notes or chords, or sound information, such as the frequency spectrum, and changes in the animation. The scenario we chose to explore is comprised of two main actors: trees and wind. Trees grow in an iterative process, and may develop leaves, while swaying in response to the wind field. The wind is represented as a vector field whose configuration and strength can be altered in real-time. Scripting then allows for synchronising these changes with musical events, providing a natural sense of harmony with the accompanying music. By having real-time access to musical information, as well as control over a reactive animation we believe to have taken a first step towards exploring a novel interdisciplinary concept with vast expressive potential.